2021
DOI: 10.15252/emmm.202114397
|View full text |Cite
|
Sign up to set email alerts
|

Characterising a homozygous two‐exon deletion in UQCRH : comparing human and mouse phenotypes

Abstract: Mitochondrial disorders are clinically and genetically diverse, with isolated complex III (CIII) deficiency being relatively rare. Here, we describe two affected cousins, presenting with recurrent episodes of severe lactic acidosis, hyperammonaemia, hypoglycaemia and encephalopathy. Genetic investigations in both cases identified a homozygous deletion of exons 2 and 3 of UQCRH, which encodes a structural complex III (CIII) subunit. We generated a mouse model with the equivalent homozygous Uqcrh deletion (Uqcrh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 91 publications
(114 reference statements)
2
8
0
Order By: Relevance
“…Uqcrh -KO mice were born with a lower Mendelian ratio and showed failure to thrive, which was particularly evident after weaning, suggesting that the metabolic disturbance exacerbates with the switch in diet from breast milk to regular chow. We measured body mass at 6, 7, 8, and 9 weeks and confirmed a previously described growth arrest (Vidali et al 2021 ) resulting in significantly lower body mass of approximately 75% (or 4–5 g less) at 6 weeks and approximately 65% (or 7–9 g less) at 9 weeks of age compared to wildtype littermate (C57BL/6 N) control mice (Table 1 ). The growth arrest was accompanied by significantly elevated blood glucose levels in Uqcrh -KO with > 25 mmol/L at 6 weeks of age, which further increased to > 29 mmol/L at 9 weeks of age compared to 3.4–9.7 mmol/L measured throughout in wildtype littermate controls (Table 1 ).…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…Uqcrh -KO mice were born with a lower Mendelian ratio and showed failure to thrive, which was particularly evident after weaning, suggesting that the metabolic disturbance exacerbates with the switch in diet from breast milk to regular chow. We measured body mass at 6, 7, 8, and 9 weeks and confirmed a previously described growth arrest (Vidali et al 2021 ) resulting in significantly lower body mass of approximately 75% (or 4–5 g less) at 6 weeks and approximately 65% (or 7–9 g less) at 9 weeks of age compared to wildtype littermate (C57BL/6 N) control mice (Table 1 ). The growth arrest was accompanied by significantly elevated blood glucose levels in Uqcrh -KO with > 25 mmol/L at 6 weeks of age, which further increased to > 29 mmol/L at 9 weeks of age compared to 3.4–9.7 mmol/L measured throughout in wildtype littermate controls (Table 1 ).…”
Section: Resultssupporting
confidence: 84%
“…Uqcrh -KO mice were generated by a two-exon deletion and show clinical signs with striking similarities, albeit a more severe phenotype compared with patients diagnosed with the corresponding deletion (Vidali et al 2021 ). As a result of the mutation, both humans and mice show marked impairment of CIII activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our predictions about 2 DAMRC-associated genes were validated by recent papers. An article published in November 2021 reported that UQCRH (Rank:8)-deficient mouse model shows impaired CIII activity [ 42 ]. ATP5MC3 (Rank:24) encodes a structural complex V (CV) subunit, and heterozygous ATP5MC3 variants were reported to reduce mitochondrial complex V activity in a paper published in October 2021 [ 43 ].…”
Section: Resultsmentioning
confidence: 99%